(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The idea behind Markov chain model and system of equations cannot be emphasized in terms of modeling physical systems like the Nigerian Current Account formation; since each finite state communicates for suitable decisions making. So this paper studied stochastic analysis of Markov chain on NCA data (2004-2022). The NCA data were transformed into 3-steps transition probability matrix solution to cover the number of independent years. From the transition matrix of stochastic analysis showed that in 2004-2012 has the highest probability of reducing in payments by 72%, the year 2005-2013 has the highest probability of reducing by 66% and finally in 2014-2022 has the highest probability of no-change in payments of goods and services by 3.3%. The future NCA data changes were known by introducing the concepts of percentages in each interval of years as column vectors where system of linear equations were developed and solutions were obtained to guide Nigerian economy on various levels of imports and exports of goods and services. Lastly, other statistical disparities were also considered and well discussed accordingly. These results are informative to Nigerian economy to effectively take vital decisions in their investment plans.